Place Attachment and Views on Tree Management - Paniotova-Maczka, Daria; Matczak, Piotr; Jabkowski, Piotr (Frontiers in Psychology, 2021)
Few studies have investigated relational environmental views of different stakeholder groups. In this study, we investigated how residents of rural and urban municipalities view the management of trees (who should decide about trees’ removal – the landowner, or the municipality), which provides a various range of ecosystem services and the extent that place attachment as a relational variable affects these views. The analysis was based on 231 questionnaires conducted in two Polish municipalities: one rural (Nysa) and one urban (Racibórz). Data were analysed using statistical methods including logistic regression models for analysing factors impacting the main research question. Our investigation showed that both place attachment involving public good sentiments and the perception of ecosystem services provided by trees, that are related to private interests significantly impacted views on tree management. In rural areas the opinion, that the municipality should decide to remove trees was positively associated with a place attachment. For residents of urban areas (Racibórz), the strength of place attachment was not related to the perception of tree removal, but it was related to the perception of trees' cultural benefits. We argue that considering psychological variables related to the tree management issues could help avoid conflicts.